The Risk Factors of Hypertension Among the Elderly in the Working Area of Sikumana Primary Health Care Center - Dida, Grace Youngest; Nayoan, Christina Rony; Sir, Amelya Betsalonia (Journal of Public Health for Tropical and Coastal Region, 2023)
Introduction: The elderly are prone to hypertension. This study aimed to analyze the risk factors of diet and physical activity for hypertension in the elderly in the working area of Sikumana Primary Health care center in 2022.Method: This analytical observation study was conducted in a case-control design. The subjects were 100 elderly (50 cases and 50 controls). Simple random sampling was used to choose the subjects. Data collection was done by interviews using structured questionnaires. Data analysis was done through the Chi-Square test and Odd Ratios.Results: The results showed that the elderly who has an unhealthy diet were 4.45 times more likely to have hypertension (OR= 4.45, 95% CI: 1.68-11.81; p=0.004). The elderly who had lacked of physical activity were 5.52 times more likely to have hypertension (OR=5.5, 95% CI: 1.86-16.34; p=0.002).Conclusion:  The risk factors for hypertension among the elderly in the working area of Sikumana Primary health care center were unhealthy diet and lack of physical activity. It is suggested that primary health care centers should promote healthy food, salt and fat reduction in the diet and increase physical activities through Posyandu (integrated health post), especially for elderly